Future of Secure Remote Workforce Perspective - What’s Next? - Balaganesh, Duraisamy (IRO Journal on Sustainable Wireless Systems, 2022)
Recently, finding a connection between changes in work habits and the controls put in place to handle cyber security threats is an innovative area of study. Surveys and conversations with subject matter experts are utilized to gather data. Since many employees struggle with the psychological and emotional aspects of working remotely, employers and information security managers are expected to continue to devote more resources to mitigating human-factor threats, which have multiplied during the COVID-19 epidemic. Consequently, the research has focused on approaches to manage or enhance security in the light of the COVID-19 pandemic's impact on present cyber threats and issues. Moreover, this article consists of various perspectives such as remote work environment, privacy authentication procedure and future security procedure.
Keywords: Cyber-security; phishing; work from home; remote work; authentication privacy